Rizzoli & Isles. the complete second season [videorecording (DVD)] - Haber, Bill; Robin, Michael M.; Tamaro, Janet; Fields, Joel; Gerritsen, Tess; Harmon, Angie, 1972-; Alexander, Sasha, 1973-; Bridges, Jordan, 1973-; Young, Lee Thompson, 1984-2013; McGill, Bruce, 1950-; Bracco, Lorraine, 1955-; Gerritsen, Tess (Rizzoli & Isles, 2012)
Homicide detective Jane Rizzoli and forensic pathologist Maura Isles are close friends, complete opposites and on the case in all 15 gritty episodes based on the best-selling novels by Tess Gerritsen. Season Two sees brash Jane healing emotional and physical scars as old loves re-appear and her mother Angela deals with divorce. Meanwhile, Jane₂s ex-con brother Tommy has eyes for cerebral Maura, whose own family life is complicated by her adoptive mother Constance.